The Potential of Mobile-Based and Pattern-Oriented Concordancing for Assisting Upper-Intermediate ESL Students in Their Academic Writing - Quan, Zhi (Auckland University of Technology, 2019)
This research was an attempt to investigate whether (and how) mobile technology and a pattern-based concordancing method, Patterns in Context (PIC), could enhance ESL students’ positive experience and uptake of DDL (Data-driven Learning). DDL is a self-directed discovery process in which learners are encouraged to study extracts of authentic texts to identify how words are used. In order to partly address the problems with DDL, the concepts of mobile DDL and PIC have been proposed and combined in this thesis. Mobile DDL aims to make DDL more accessible and appealing to students at large by utilising new affordances of mobile technology. PIC is designed to search and retrieve patterns, a multi-word unit which combines lexical choices and grammatical forms, so as to provide more easily observable search results. This adapted DDL was used to assist ESL students in academic writing in this research. This research was cross-disciplinary, involving corpus linguistics, technology-enhanced language education and software engineering. Based on the overarching worldview of pragmatism, it adopted a design of action research with mixed methods. Over the three phases of the research, 58 voluntary participants in total were involved to experience and evaluate the two specifically developed mobile apps, which underwent continuous changes and improvements according to their feedback and requests. The mixed methods to collect qualitative and quantitative data included automatic logging, questionnaires, interviews and focus groups. Triangulated data revealed that PIC, as an alternative concordancing method, was advantageous over KWIC in efficiency, perceived effectiveness and user acceptance. The participants were in general positive about their experience working with the apps, and they seemed to have high requirements involving technical affordances and great expectations for mobile learning. Finally, it can be concluded that upper-intermediate ESL students’ positive experience and uptake of using concordancing to help with academic writing can be enhanced by mobile-based concordancing tools and the pattern-oriented search and retrieval approach of PIC. The benefits of mobile DDL and PIC imply that DDL can be made more accessible and acceptable to students by incorporating emerging technologies and findings of applied linguistics.
Keywords: Data-driven learning (DDL); Mobile learning; Academic writing; Pattern grammar; Corpus linguistics